How about now : poems - Baer, Kate (Harper, an imprint of HarperCollins Publishers, 2025)
"[The poet Kate] Baer explores what it means to grow older, to release children into the wildness of their own lives, and to reclaim the ever-evolving self. Raw, luminous, and urgent, these poems channel Baer's own journey to middle age into poems that are profoundly intimate yet resound universally, identifying the beauty, resilience, and fragility that arrive in every stage of life"--